Role and importance of choreography in gymnastic and dance sports - Artemyeva, G.; Moshenska, T. (Slobozhanskyi herald of science and sport, 2018)
Choreographic component is mandatory for the construction of competitive programs in gymnastic and dance sports, and when presenting an assessment for the performed composition, choreography is one of the criteria, according to one of the types of training in these sports there is choreographic.